2020
DOI: 10.1111/1750-3841.14992
|View full text |Cite
|
Sign up to set email alerts
|

Microbial composition of Kombucha determined using amplicon sequencing and shotgun metagenomics

Abstract: Kombucha, a fermented tea generated from the co-culture of yeasts and bacteria, has gained worldwide popularity in recent years due to its potential benefits to human health. As a result, many studies have attempted to characterize both its biochemical properties and microbial composition. Here, we have applied a combination of whole metagenome sequencing (WMS) and amplicon (16S rRNA and Internal Transcribed Spacer 1 [ITS1]) sequencing to investigate the microbial communities of homemade Kombucha fermentations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 77 publications
6
64
0
6
Order By: Relevance
“…Prior to this study, Starmerella , one of the major fungi replacing Brettanomyces in Cluster II, had not been described in molecular ecology studies of the solid-phase Kombucha SCOBY. Starmerella is a relatively new genus into which several Candida species have been reclassified [ 72 ], thus earlier Kombucha studies reporting Candida at genus level may have observed species currently classified as Starmerella . Starmerella davenportii , detected in the ‘meta’-SCOBY, was recently isolated from Kombucha and shown to generate volatile aroma compounds and organic acids during a black tea fermentation [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this study, Starmerella , one of the major fungi replacing Brettanomyces in Cluster II, had not been described in molecular ecology studies of the solid-phase Kombucha SCOBY. Starmerella is a relatively new genus into which several Candida species have been reclassified [ 72 ], thus earlier Kombucha studies reporting Candida at genus level may have observed species currently classified as Starmerella . Starmerella davenportii , detected in the ‘meta’-SCOBY, was recently isolated from Kombucha and shown to generate volatile aroma compounds and organic acids during a black tea fermentation [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shotgun metagenomics allows to overcome the challenges that affect both assembly based and mapping‐based metagenomic profiling (Laudadio et al ., 2019), particularly, of high‐complexity samples (Walsh et al ., 2016; Seol et al ., 2019; Sirén et al ., 2019), including KMC (Arıkan et al ., 2020; Villarreal‐Soto et al ., 2020). Hence, we have implemented a shotgun metagenomic approach to gather an unbiased snapshot of the community structure and potential functionality in KMC that were previously exposed to space and different levels of Mars‐like conditions, simulated on low Earth orbit outside the International Space Station (ISS), within the BIOMEX project (de Vera et al ., 2019; Podolich et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The study proved that shotgun sequencing technology could be used to evaluate the microbial community composition during beef production, as well as pathogen population shifts ( Yang et al, 2016 ). Several studies have shown that shotgun sequencing technology is also applicable to the study of microbial communities in food or beverages that require fermentation ( Ferrocino et al, 2018 ; Arikan et al, 2020 ), as well as human microbes found in the skin ( Oh et al, 2014 ), saliva ( Hasan et al, 2014 ), and gastrointestinal tract ( Vangay et al, 2018 ; Zhao et al, 2018 ). In addition to research in the field of microbiology, shotgun sequencing technology has also been successfully used in animal diet analysis ( Srivathsan et al, 2015 ), animal diversity ( Zhou et al, 2013 ), and ingredient identification in food ( Haiminen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%